"We Should Talk"—Moving knowledge into action by learning to engage patients, families, and healthcare staff to communicate for patient safety. Issue 4 (July 2016) - Dubrovsky, Alexander Sasha; Bishop, Andrea; Biron, Alain; Cunningham-Allard, Gabrielle; DeCivita, Frederick; Fima, Aaron; Korah, Nadine; Marchionni, Caroline; Proulx, Marie Claude; Toman, Pamela; Tsirgiotis, Stephanie; Zavalkoff, Samara
Innovation in patient engagement and empowerment has been identified as a priority area in the Canadian healthcare system. This article describes the development and implementation of the We Should Talk campaign at an academic pediatric hospital. Through the use of a guiding theoretical framework and a multidisciplinary project team, a multimedia campaign was designed to inspire staff, patients and families to effectively communicate to improve patient safety. The We Should Talk campaign provides a case study for how an organization can foster frontline improvement through the engagement of patient, families, and healthcare providers.